Technical and Financial Feasibility of Aromatherapy Pillow (Talophy) Production: A Sheep Wool Waste Utilization Venture - Muhammad Surya Fadhlurrohman; Andriyono Kilat Adhi; Nunung Kusnadi (School of Business, IPB University (SB-IPB), 2023)
TALOPHY or aromatherapy pillow made from sheep's wool is an innovative product as a result of PKM 2020 activities. THALOPY is a new innovative product on the market, but the problem that occurs is the availability of raw sheep's wool which can only be obtained within a period of four months. Therefore, this study aims to analyze the technical and financial feasibility of the TALOPHY business plan. The methods used in this study are qualitative analysis on technical aspects and quantitative analysis on financial analysis. Technical aspects include business location, production scale, machine selection, production process, and the type of technology used. The financial aspect uses investment criteria including NPV, IRR, PP, and switching value analysis. The results of the study show the feasibility of the technical aspects, including the geographical location of the business, namely in Jatisari Village, Madiun Regency, East Java province; the availability of sheep wool is limited, namely only 800 kg every 4 months; the production scale is 200 pillows for one production (every 2 months); the production process of the TALOPHY business uses an intermittent or gradual method; the business layout facilitates production activities; and the technology is used as needed. Based on the results of the eligibility criteria, the TALOPHY business investment is not feasible to run. This is based on the NPV obtained for IDR 27,384,206, a net B/C of 1.3, an IRR of 4%, and a PP of 11 years and 8 months. The results of the switching value analysis show that the most sensitive factor or determinant of TALOPHY's business feasibility is a decrease in sales and a decrease in product prices, with a value of 1.63%. Keywords: financial analysis, switching value analysis, technical analysis, sheep wool, insomnia